THERAPEUTIC STRATEGIES FOR SUBPROSTHETIC MUCOSAL COMPLICATIONS ASSOCIATED WITH REMOVABLE DENTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The oral mucosa has a number of properties, making it resistant to various external influences, including physical, thermal and chemical factors. One of the most important properties of the mucosa is its strong regenerative ability. At the same time, despite the protective and biological functions of the oral mucosa, various diseases are widespread, and their treatment is one of the most complex and urgent issues in dentistry. According to WHO, more than 90% of the population over middle age suffer from diseases of the oral mucosa and periodontal tissues.